2013
DOI: 10.1093/europace/eut021
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon ablation of paroxysmal atrial fibrillation: 5-year outcome after single procedure and predictors of success

Abstract: Sinus rhythm can be maintained in a substantial proportion of patients with PAF even 5 years after circumferential PVI using CB ablation. The rate of decline in freedom from AFLAT was highest within the first 12 months after the index procedure. The patients with enlarged left atrium and/or impaired renal function have lower outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 30 publications
6
48
1
Order By: Relevance
“…Electrical remodelling and structural remodelling are the main mechanisms of AF, and the burden of AF will not only deteriorate the remodelling but also change it to persistent AF. Therefore, some studies have suggested that for the increased LAD and long duration of AF, early intervention and upstream treatment after PVI can effectively relieve or prevent late recurrence [19]. The "dangerous" size of the LAD is different between patients and measurement methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical remodelling and structural remodelling are the main mechanisms of AF, and the burden of AF will not only deteriorate the remodelling but also change it to persistent AF. Therefore, some studies have suggested that for the increased LAD and long duration of AF, early intervention and upstream treatment after PVI can effectively relieve or prevent late recurrence [19]. The "dangerous" size of the LAD is different between patients and measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding non-compliant documents, only 16 articles were included in this study. In the remaining 16 articles [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], ERAF, LAD, AF duration, and persistent AF were mentioned 14, eight, six, and four times, respectively. There were three retrospective studies, 12 prospective studies, and one case-control study in the final 16 articles.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…We read with interest the paper by Koźluk et al [1], which brings several points about multi--electrode duty-cycled radiofrequency ablation: -The outcome in patients with paroxysmal atrial fibrillation (AF) was lower when compared to 1-and 5-year follow-up after single cryoballoon ablation procedure performed with higher follow-up regime (7-and not 1-day Holter ECG) [2]. Most triggers originate in left atrium (LA)-pulmonary vein (PV) junction [3].…”
Section: Atrial Fibrillation Ablation: Limitations Of Pulmonary Vein mentioning
confidence: 99%
“…The procedure was previously described [3,6]. After the transseptal punctures were performed, heparin was introduced with the aim of keeping the activation clotting time > 300 s throughout the whole procedure.…”
Section: Intervention and Post-ablation Managementmentioning
confidence: 99%
“…This parameter is likely involved in the PV reconduction process, especially at PV with difficult geometries [11]. Optimization of tissue contact may require utilization of technical maneuvers [11,12], different sized balloons [3,6,8,13], and "touch-up" focal lesions [3,6,8,[13][14][15]. Moreover, peri-procedural PNP results in abrupt interruption of cryoenergy application by an operator which can be the next cause of not-complete acute PVI success.…”
Section: Acute Successmentioning
confidence: 99%